Software Analytics in Practice - Zhang, Dongmei; Han, Shi; Dang, Yingnong; Lou, Jian-Guang; Zhang, Haidong; Xie, Tao (IEEE Software, Special Issue on the Many Faces of Software Analytics, 2013)
Software analytics is to utilize data-driven approaches to enable software practitioners to perform data exploration and analysis in order to obtain insightful and actionable information for completing various tasks around software systems, software users, and software development process. In this article, we present how we worked on the StackMine project, a successful software analytic project that produced an analytic system used by and transferred to Microsoft product teams. We also discuss the lessons learned from StackMine on applying software analytics technologies to make practice impact – solving problems that practitioners care about, using domain knowledge for correct data understanding, building prototypes early to get practitioners’ feedback, taking scalability and customizability into account, and evaluating analysis results using criteria related to real tasks.